2019
DOI: 10.3390/met9030355
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of the Heat Input Effect on the Mechanical Properties and Microstructure of Dissimilar Weld Joints of 690-MPa QT and TMCP Steel

Abstract: The study evaluates numerically and experimentally the effect of welding heat input parameters on the microstructure and hardness of the heat-affected zone (HAZ) of quenched and tempered (QT) and thermo-mechanically controlled process (TMCP) 690-MPa high-strength steel. Numerical analyses and experimental comparisons were applied using three heat input values (10, 14, and 17 kJ/cm) in order to predict the thermal fields during welding. Experimental analysis was carried out of the microstructure and microhardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The HAZ has undergone recrystallization and grain growth processes, both of which are affected by the transient and high-temperature characteristics of the welding process, and numerical simulation methods can reproduce this process well [ 12 ]. Bayock et al [ 13 ] studied the effect of heat input on the mechanical properties and microstructure of dissimilar welded joints of 690 MPa steel through numerical simulation. The results show that the welding heat input should be reasonably controlled and limited, especially for thick plates, because the softening effect of welded joints is proportional to the thickness of plates.…”
Section: Introductionmentioning
confidence: 99%
“…The HAZ has undergone recrystallization and grain growth processes, both of which are affected by the transient and high-temperature characteristics of the welding process, and numerical simulation methods can reproduce this process well [ 12 ]. Bayock et al [ 13 ] studied the effect of heat input on the mechanical properties and microstructure of dissimilar welded joints of 690 MPa steel through numerical simulation. The results show that the welding heat input should be reasonably controlled and limited, especially for thick plates, because the softening effect of welded joints is proportional to the thickness of plates.…”
Section: Introductionmentioning
confidence: 99%
“…Besides increasing the strength and toughness properties, the development of weldability characteristics also plays an important role in steel producers. However, the determination of the right welding technology, including the optimal process window, may still cause difficulties for welding engineers [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…An experiment was carried out to determine the usability of welded HSS S960QC in arctic regions (where the ambient temperature is approximately −25 • C to −30 • C during winter). The researchers found that using a heat input of 5 to 6.5 kJ/cm increased the hardness but caused a brittle fracture in the HAZ of the weld joints [17][18][19]. To avoid this undesirable phenomenon, preheating and post-weld heat treatment of the weld joint during the welding process are required.…”
Section: Introductionmentioning
confidence: 99%